ANALYSIS OF INFANT MORTALITY IN THE TERRITORY OF THE REPUBLIC OF ALTAI - Пелеганчук, Владимир Алексеевич; Трибунский, Сергей Иванович; Колядо, Владимир Борисович; Колядо, Елена Владимировна (Medicine in Kuzbass, 2018)
The object of research (observation) was the cohort of the children born alive but deceased during the first year of life in the territory of the Republic of Altai in 2012-2016.Purpose of research. The analysis of the dynamics of infant mortality, and also the mortality during the early neonatal, neonatal and post-neonatal periods of life in the Republic of Altai.Statistical processing of the obtained results. In the study, there was applied the technology of statistical processing and methods of the analysis of the dynamics of the same group of indices for the 5-year period. For a validated assessment of the development of phenomena in time, an analytical indicator was calculated namely annual average rate of increase. For the research of the interrelation of the two variables, the method of parametric statistics was used: Pearson correlation coefficient.Basic results. In the Republic of Altai within the period 2012-2016, a decrease in infant mortality has been observed with an annual average rate of decrease 5.9 %. During the correlation analysis, there was revealed a direct, strong, statistically reliable interrelation of the level of infant mortality with the indicator of specific weight of the children deceased during the post-neonatal period, i.e. the number of the deceased children decreases from the 29th day to 1 year of life, while during the neonatal period an increase in mortality was registered.Field of the application. Organization of medical activities.Inferences. Further reduction of the infant mortality rate should be aimed at decreasing neonatal mortality by reducing losses from the conditions occurring in the perinatal period, further decreasing congenital anomalies and malformations, as well as weakening the medical and social factors affecting this indicator.
Keywords: infant mortality; early neonatal mortality; later neonatal mortality; post-neonatal mortality; the Republic of Altai